Constraints faced by the farmers in production and marketing of vegetables in Haryana - KUMAR, AJAY; SUMIT, SUMIT; YADAV, MUKESH KUMAR; ROHILA, ANIL KUMAR (The Indian Journal of Agricultural Sciences, 2019)
India is the largest producer of vegetables in the world after China. The cauliflower, potato, radish, tomato, onionare the major vegetables cultivated in Haryana. Present study was conducted in Haryana to study the constraintsfaced by farmers and middlemen in production and marketing of major vegetables. Study was carried out in Sonipatfor cauliflower, Yamunanagar for Potato, Ambala for onion, Karnal for tomato, Gurugram for radish. Present studyfully relies on the primary data and hence data was collected through proper structured schedule for the productionyear 2014-15. Major production related constraints expressed by vegetable growers were lack of information aboutcultivation of vegetables, higher cost of fertilizers, seeds and labour and their unavailability when needed, lack ofsuitable cold storage facilities, high cost of storage, costly weedicides, spurious plant protection chemicals, and lackof credit. Major marketing related constraints expressed in marketing of vegetables were lack of market information,higher price fluctuation, higher amount of price spread, malpractices in weighing and storing of vegetables, problem ofstorage facilities, lack of processing industries/units, higher price fluctuations, high cost of labour, high transportationcost, and delay in payments.